DISCUSSION OF DEFINITIONS AND TERMINOLOGY PROBLEMS OF TECHNICAL CONTROL - SMOLIN, Yurii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The directions of development of control as a scientific branch are considered. It is shown that the variety of definitions of control goes beyond terminological inconveniences and hinders communication of specialists and their creative search, and this necessitates the development of a single approach and a single terminology in the theory of control. A detailed analysis of the existing views of experts on control, the results of their discussions and changes in approaches to terminology that existed in previous years and have developed at this time. The analysis of literature sources on the problems of definitions and terminology of technical control is given. Most of the existing dictionary definitions of control and technical control, as well as their modern interpretations are given and analyzed. There are two main forms of technical control: passive and active control. The terminology related to passive and active control is considered and analyzed, taking into account the methods after operational and technical control. It is shown that the universality and capacity of the term control contributed to its penetration into various spheres of human activity, including technology. Control is defined as a generic concept, and this interpretation for the needs of quantitative research has been translated into mathematical language in terms of set theory. An isomorphic mathematical model of the physical model of the object of control is given, in which the nature of the object of control is not specified, ie it can be technical, economic, biological, etc. The parameters of technical objects of control of the corresponding offered model are also given. It is shown that in terms of control capabilities the main interest is its methodological component, which expresses the essence of control, determines its specific varieties. The results of control of technical and other objects as the necessary information base of this or that production procedure are considered: rejection, sorting, protection. It is proved that when the control results are used to control the technological object, in this case it is not the control of the source object, but the controlled process and the process itself is now the object of control, but not the object of control. Thus, the more developed form of participation of control in management of technological object is its active control.